The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/micro3020034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pharmaco-Technological Parameters of Solid Lipid Nanoparticles as Carriers for Sinapic Acid

Abstract: Sinapic acid, 3,5-dimethoxyl-4-hydroxycinnamic acid, belonging to the class of hydroxycinnamic acids, shows antioxidant, anti-inflammatory, anticancer, hepatoprotective, cardioprotective, renoprotective, neuroprotective, antidiabetic, anxiolytic, and antibacterial activity. The aim of this work was to incorporate sinapic acid into solid lipid nanoparticles in order to improve its bioavailability. SLNs were prepared using the hot high-speed homogenization method. The pharmaco-technological properties and thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…SA has also shown metal chelating potential, anti-inflammatory, antibacterial, antihyperglycemic, antimicrobial, anxiolytic, and tumor-fighting activities, peroxynitrite and free-radical scavenging, plus antihypertensive and cardiovascular remodeling , (Figure ). It is shown that SA’s poor solubility, hydrophobic nature, low in vitro dissolution rate, reduced oral bioavailability, and enhanced lipophilicity due to the esterification are responsible for its limited therapeutic potential whereas the increased lipophilicity results in higher affinity for the lipophilic phase of certain drug delivery systems and the cell membrane. In this regard, several studies have been performed to investigate the possible strategies for a more effective delivery of SA for therapeutic purposes. SA encapsulation in various nano delivery systems including solid lipid nanoparticles, glucosamine nanoparticles, ethosomes, transferosomes, and liposomes has been shown to be a promising technique to overcome SA’s lack of solubility and bioavailability contributing to their interesting properties like high biocompatibility, protected drug release, and cross-skin permeability which lead to efficient penetration of the embedded molecule into the target site and a better therapeutic result. ,,, …”
Section: Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…SA has also shown metal chelating potential, anti-inflammatory, antibacterial, antihyperglycemic, antimicrobial, anxiolytic, and tumor-fighting activities, peroxynitrite and free-radical scavenging, plus antihypertensive and cardiovascular remodeling , (Figure ). It is shown that SA’s poor solubility, hydrophobic nature, low in vitro dissolution rate, reduced oral bioavailability, and enhanced lipophilicity due to the esterification are responsible for its limited therapeutic potential whereas the increased lipophilicity results in higher affinity for the lipophilic phase of certain drug delivery systems and the cell membrane. In this regard, several studies have been performed to investigate the possible strategies for a more effective delivery of SA for therapeutic purposes. SA encapsulation in various nano delivery systems including solid lipid nanoparticles, glucosamine nanoparticles, ethosomes, transferosomes, and liposomes has been shown to be a promising technique to overcome SA’s lack of solubility and bioavailability contributing to their interesting properties like high biocompatibility, protected drug release, and cross-skin permeability which lead to efficient penetration of the embedded molecule into the target site and a better therapeutic result. ,,, …”
Section: Chemical Propertiesmentioning
confidence: 99%
“…SA encapsulation in various nano delivery systems including solid lipid nanoparticles, glucosamine nanoparticles, ethosomes, transferosomes, and liposomes has been shown to be a promising technique to overcome SA's lack of solubility and bioavailability contributing to their interesting properties like high biocompatibility, protected drug release, and cross-skin permeability which lead to efficient penetration of the embedded molecule into the target site and a better therapeutic result. 36,37,39,40…”
Section: Chemical Propertiesmentioning
confidence: 99%